The Effect of Seed Priming and Soaking Durations with Di Ammonium Phosphate (DAP) on Seedling Emergence and Morphological Traits in Okra (Hibiscus esculentus L.) - Shafi, Gohar; Ara, Neelam; Khan, Fahim Ullah (International Journal of Environment, 2014)
The experiment was conducted at Ornamental Horticulture Nursery of the University of Agriculture, Peshawar in July 2008 to study the effect of okra seed priming with different phosphorus concentrations (DAP) at various durations on seedling emergence and some related traits. The experiment was laid out in Randomized Complete Block Design in split plot arrangement, with three replications. Four DAP concentrations i.e. 0.5%, 1%, 1.5%, 2%with difference soaking durations from 0 to 48 hours with 4 hours interval. Germination percentage (%), survival percentage (%), number of days to emergence, number of days to first flowering, plant height (cm), were significantly affected by concentrations and soaking durations. Mean values showed that maximum germination percentage (70.49 %), maximum plant height (150.33 cm) was observed in plot in which seeds were soaked in 0.5% phosphate solution. It is concluded that phosphorus concentration of 0.5 % and soaking for 32hour are recommended for seed priming in okra. DOI: http://dx.doi.org/10.3126/ije.v3i3.11068 International Journal of Environment Vol.3(3) 2014: 113-125